Analisis Perbandingan Toolkit Puran File Recovery, Glary Undelete Dan Recuva Data Recovery Untuk Digital Forensik - Handrizal, Handrizal (STIKOM Tunas Bangsa Pematangsiantar, 2017)
This paper presents a comparative analysis of three digital forensics toolkit for data recovery scenario that has been deleted. Toolkit used is Puran File Recovery, Glary Undelete and Recuva Data Recovery. Their ability to restore deleted data has been tested and analyzed in a USB flash drive. The results of the comparison show that this third toolkit can work well in terms of finding the data that has been deleted or in recovering the deleted data.